Effect of eccentric contractions with a pre-exercise glycogen depletion protocol on metabolic responses during submaximal cycling - Gavin, J. P.; Myers, S. D.; Clements, R. E.; Willems, M. E. T. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Glycogen depletion following prolonged exercise is often associated with susceptibility to, and recovery from, exerciseinduced muscle damage (EIMD). In a state of EIMD, cardiorespiratory responses may become compromised during subsequent moderate- and high-intensity cycling. Yet, the effects on metabolic and cardiorespiratory responses during low-intensity cycling are unclear. Methods: Ten men (22±3 yr, 180±7 cm, 81±16 kg) exercised at 60 rpm for 10-min on a cycle ergometer at 50% maximal oxygen uptake prior to, and 12-hr after completing 100 unilateral maximal voluntary eccentric contractions with knee extensors of each leg. The evening before the eccentric bout, a unilateral glycogen depleting protocol (Pilegaard et al., 2002) was performed to lower muscle glycogen in the right leg. Eccentric contractions were performed on an isokinetic dynamometer (Humac Norm, USA) from full knee extension to flexion (1.57 rad/s). Cardiorespiratory responses were recorded using a portable metabolic cart (Cosmed K4b2, Italy) during cycling, with fat and carbohydrate oxidation calculated using stoichiometry equations (Jeukendrup & Wallis, 2005). Changes in maximal isometric voluntary force (MVIF) were used to assess EIMD. Paired samples t-tests were used to detect difference in pre- and post-values for MVIF, and metabolic and cardiorespiratory measures during the last minute of exercise. Results: Twelve hours post, EIMD was evidenced by MVIF reductions of: 7% (left leg; P=0.06) and 8.3% (right leg; P=0.008). Respiratory exchange ratio reduced from 0.97±0.05 to 0.92±0.05 (P=0.02), while oxygen uptake (1.5±0.2 to 1.6±0.2 L/min, P=0.39), carbon dioxide output (1.4±0.3 to 1.4±0.2 L/min, P=0.54), minute ventilation (36.9±0.7 to 38.1±0.6 L/min, P=0.69) and heart rate (110±2 to 111±2 beats/min, P=0.85) were similar. Fat oxidation increased post from 0.16±0.1 to 0.26±0.1 g/min (P=0.05), but carbohydrate oxidation was unchanged (1.6±0.3 to 1.4±0.4 g/min, P=0.36). Discussion: Eccentric exercise preceded by a unilateral glycogen depleting protocol altered metabolic responses during lowintensity cycling exercise. Increased fat oxidation may be due to impaired insulin action with EIMD; but this was not supported by cardiorespiratory responses. Such may be attributable to limited damage induced by the eccentric bout, the intensity of the cycling exercise or a combination of both. Regardless, the design may have utility in examining mechanisms underpinning the physiological responses to exercise in an EIMD state.